1974
DOI: 10.1042/bj1390351
|View full text |Cite
|
Sign up to set email alerts
|

Specific inhibition of the enzymic decarboxylation of S-adenosylmethionine by methylglyoxal bis(guanylhydrazone) and related substances

Abstract: Methylglyoxal bis(guanylhydrazone) {1,1'-[(methylethanediylidene)-dinitrilo]diguanidine} is a very potent inhibitor of putrescine-activated S-adenosylmethionine decarboxylases from many different mammalian tissues, including sublines of mouse L1210 leukaemia that are resistant to the drug as well as sublines that are sensitive. The inhibition of purified rat ventral prostate S-adenosylmethionine decarboxylase is competitive with respect to the S-adenosylmethionine substrate, and is much greater in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
0
2

Year Published

1980
1980
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(47 citation statements)
references
References 21 publications
7
38
0
2
Order By: Relevance
“…To determine whether L. pneumophila requires the activity of host SAMDC during intracellular growth in mammalian cells, we infected cells treated with two inhibitors of polyamine biosynthesis. MGBG acts as a specific, competitive, and irreversible inhibitor of SAMDC (19,88,90), and DFMO is an irreversible inhibitor of ornithine decarboxylase (56,70), an enzyme required for the synthesis of putrescine, a precursor of spermidine. We initially found that treatment of mouse L929 cells with MGBG significantly inhibited L. pneumophila intracellular replication at 24 and 48 h postinfection, whereas DFMO inhibition was significant only at 48 h postinfection (Fig.…”
Section: Htpb Reaches the Cytosol Of L Pneumophila-infected Cellsmentioning
confidence: 99%
“…To determine whether L. pneumophila requires the activity of host SAMDC during intracellular growth in mammalian cells, we infected cells treated with two inhibitors of polyamine biosynthesis. MGBG acts as a specific, competitive, and irreversible inhibitor of SAMDC (19,88,90), and DFMO is an irreversible inhibitor of ornithine decarboxylase (56,70), an enzyme required for the synthesis of putrescine, a precursor of spermidine. We initially found that treatment of mouse L929 cells with MGBG significantly inhibited L. pneumophila intracellular replication at 24 and 48 h postinfection, whereas DFMO inhibition was significant only at 48 h postinfection (Fig.…”
Section: Htpb Reaches the Cytosol Of L Pneumophila-infected Cellsmentioning
confidence: 99%
“…ACC as an immediate precursor of ethylene 13 ) and NAA induced as the same levels of sterility as that in the control. Spermine and MGBG, 14,15) which are related to the regulation of ethylene production, induced sterility similar to that in the control. Azetidine-2-carboxylic acid, which is an analogue of azetidine-3-carboxylic acid that induced male sterility in wheat, 3) produced no effect on sterility in rice.…”
Section: Effects Of Twelve Chemicals On Sterility In Ricementioning
confidence: 87%
“…La S-adenosylmethionine decarboxylase (SAMDC), qui transforme Ia SAM en SAM decarboxylee {donneuse de groupements aminopropyles), est inhibee par le methylglyoxal-bis-{guanylhy-drazone) (MGBG), qui est un inhibiteur competitif in vitro et in vivo (WilliamsAshman et Schenone, 1972 ;Corti et al, 1974 (Sunkara et al, 1977;Heby 1981), puis dans les cellules vegetales (Flores et Galston, 1982 ;Martin-Tanguy, 1985;Bagni 1988 (Taboret Tabor, 1976;Pegg et Me Cann, 1982). L'activite de l'ODC est corrclce positivement avec Ia division cellulaire dans les cultures de cellulcs de tabac alors que celle de I'ADC se trouve tres reduite (Heimer et al, 1979).…”
Section: Metabolisme Des Polyaminesunclassified